2019
DOI: 10.2147/cia.s194880
|View full text |Cite
|
Sign up to set email alerts
|

Transtrochanteric approach can provide better postoperative care and lower complication rate in the treatment of hip fractures

Abstract: PurposeDislocation is an important complication that increases the mortality, morbidity, and postoperative care following bipolar hemiarthroplasty. It is thought that the transtrochanteric approach that enables access to the femoral neck directly from the fracture line at the coronal plane of the greater trochanter without opening the posterior and anterior capsules could reduce the risk of dislocation. Additionally, it is argued that preservation of the external rotators could also be advantageous for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…A series of 15 studies investigating surgery-related fracture complications were reported. Pooling data from 3 studies (20,26,32) comparing LA and AA did not reveal statistically significant differences (OR: 0.56 95% CI: 0.16-1.98 I 2 = 0% P = 0.37 Figure 8A), while 8 studies (19, 23,27,29,34,36,42,43) analyzed PA and LA (OR: 0.87 95% CI: 0.55-1.36 I 2 = 0% P = 0.53 Figure 8B), and another 4 (22,39,44,45) compared LA with AA (OR: 0.71 95% CI: 0.18-2.79 I 2 = 0% P = 0.62 Figure 8C).…”
Section: Fracturesmentioning
confidence: 86%
See 3 more Smart Citations
“…A series of 15 studies investigating surgery-related fracture complications were reported. Pooling data from 3 studies (20,26,32) comparing LA and AA did not reveal statistically significant differences (OR: 0.56 95% CI: 0.16-1.98 I 2 = 0% P = 0.37 Figure 8A), while 8 studies (19, 23,27,29,34,36,42,43) analyzed PA and LA (OR: 0.87 95% CI: 0.55-1.36 I 2 = 0% P = 0.53 Figure 8B), and another 4 (22,39,44,45) compared LA with AA (OR: 0.71 95% CI: 0.18-2.79 I 2 = 0% P = 0.62 Figure 8C).…”
Section: Fracturesmentioning
confidence: 86%
“…Dislocation was the most disparate outcome in the metaanalysis and an essential indicator for evaluating the results of the surgery. The PA is at greater risk of dislocation than the other two approaches and may be related to surgical incision of soft tissue anatomy such as the capsule, short external rotators, and piriformis (49).There may also be a relationship with patient cognitive status and sex, with some findings of higher dislocation rates in women and patients with cognitive impairment (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservative treatment has a limited place; the main treatment for hip fractures is surgery [10]. ITFs are observed 3 times more than CFFs [11]. The surgical approach to CFFs has gained clarity in the literature [12], while surgical indication in ITFs is still controversial [13].…”
Section: Discussionmentioning
confidence: 99%